1961
DOI: 10.1172/jci104320
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Infusions of Chlorothiazide on Urinary Dilution and Concentration in the Dog

Abstract: It has been observed that the saluretic agent chlorothiazide (6-chloro-7-sulfamyl-1,2,4-benzothiadiazine-1,1 dioxide) and its analogs produce alterations in the process of urinary dilution which differ from those expected from a simple increase in electrolyte excretion (1-3). Heinemann, Demartini and Laragh (2) observed in human subjects undergoing water diiuresis that the augmented electrolyte excretion resulting from the injection of chlorothiazide was associated with no increase, or a fall, in the clearanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
1
1

Year Published

1964
1964
1992
1992

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(79 citation statements)
references
References 16 publications
8
69
1
1
Order By: Relevance
“…The ability of normal subjects studied to maintain TCH2O for a given Cosm shortly after the peak of osmotic diuresis is consistent with the findings in normal dogs (12 abnormal in the present studies.…”
Section: Methodssupporting
confidence: 90%
“…The ability of normal subjects studied to maintain TCH2O for a given Cosm shortly after the peak of osmotic diuresis is consistent with the findings in normal dogs (12 abnormal in the present studies.…”
Section: Methodssupporting
confidence: 90%
“…Clearance and micropuncture studies have suggested that the main sites of action of chlorothiazide are in the cortical portion of the ascending limb of Henle's loop and the distal convoluted tubule (24,25). If Ringer loading inhibited sodium transport in this chlorothiazide-sensitive portion of JMN to a greater extent than in SN, administration of this diuretic may reduce or abolish the net addition pattern.…”
Section: Resultsmentioning
confidence: 99%
“…7), although reduced to 0.4, was still significant at P < 0.01. 6 of the 44 points illustrated in Fig. 7 have a TF/UFca ratio of more than twice the population mean.…”
Section: Clearance Datamentioning
confidence: 90%
“…Furosemide has also been reported as having no proximal effect in the rhesus monkey (40), although a more specific response has been demonstrated in the rat proximal tubule (41) The action of thiazides in more distal nephron segments has been more clearly elucidated, although much of the evidence is indirect. Several investigators have reported that thiazides reduce free water clearance (CH20) and have no effect on free water reabsorption (44)(45)(46). The usual interpretation has been that thiazides inhibit sodium reabsorption in the diluting segment in the ascending limb of Henle's loop.…”
Section: Clearance Datamentioning
confidence: 99%